2015
DOI: 10.17795/ijcp-4019
|View full text |Cite
|
Sign up to set email alerts
|

Preventing and Therapeutic Effect of Propolis in Radiotherapy Induced Mucositis of Head and Neck Cancers: A Triple-Blind, Randomized, Placebo-Controlled Trial

Abstract: Background:Mucositis is one of the acute complications of radiotherapy which can ulcerate oral mucosa and cause severe pain and discomfort which can affect oral normal function. Propolis is a natural source of flavenoid which has antiulcer, antibacterial, antifungal, healing and anti-inflammatory effects. Using such an affordable compound without any bad smell or taste that has reasonable price can help the radiotherapy undergoing patients.Objectives:Our goal is assessing the preventing and therapeutic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 15 publications
1
26
0
7
Order By: Relevance
“…There are also reports claiming that propolis reduces oral mucositis in patients undergoing radiotherapy. Research conducted by Javadzadeh Balouri et al confirmed that propolis prevents and is efficient in treating radiotherapy-induced mucositis [ 34 ]. Another significant activity of propolis is its antiviral effect.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports claiming that propolis reduces oral mucositis in patients undergoing radiotherapy. Research conducted by Javadzadeh Balouri et al confirmed that propolis prevents and is efficient in treating radiotherapy-induced mucositis [ 34 ]. Another significant activity of propolis is its antiviral effect.…”
Section: Discussionmentioning
confidence: 99%
“…Propolis is a natural product collected by honeybee worker, and contains flavonoids with anti-ulcer, anti-bacterial, anti-fungal, healing and anti-inflammatory effects (Dodwad and Kukreja, 2011 ). Its water extract mouthwash efficiently prevents and heals chemotherapy or radiotherapy-induced oral mucositis in patients with head and neck cancers, or leukemia (Javadzadeh Bolouri et al, 2015 ; Eslami et al, 2016 ). However, early report of a double blind randomized placebo controlled trial shows that propolis cannot be recommended for severe oral mucositis in chemotherapy-treated pediatric patients (Tomazevic and Jazbec, 2013 ).…”
Section: Prevention Of Oral Mucositis Partly By Reducing Oxidative Stmentioning
confidence: 99%
“…Although this was a double‐blind study, the limited (N = 40) number of randomized patients and the lack of correction for the individual amount of mucosa included in the radiotherapy fields weakened the conclusions. In a randomized blind study on only 20 patients undergoing radiotherapy for head and neck cancer, patients receiving propolis mouthwashes had significantly lower grades of mucositis . In a more recent phase III study on a larger population (N = 40) treated with chemotherapy only, propolis was found to favorably impact mucosa healing after treatment but not the incidence of mucositis during treatment .…”
Section: Discussionmentioning
confidence: 93%